Harnessing Africa’s Potentials For Economic Transformation And Social Inclusion In A Dynamic Global Economy - Nyerhovwo Kingsley Erakpotobor (International Journal of Economics and Development, 2026)
Africa holds vast natural and human resource potential, yet its economic transformation remains constrained by institutional weaknesses, high inequality, and vulnerability to global shocks.  Achieving inclusive and sustainable development requires localized, evidence-based strategies tailored to the continent’s diverse realities. This study examines the impact of sustainable development strategies on Africa’s economic transformation, explores effective country-specific models for inclusive growth, and evaluates the role of governance, trade, and innovation in promoting social inclusion. The research is anchored in Sustainable Development Theory, which emphasizes the need for balanced economic growth, social equity, and environmental responsibility-principles that guide this study’s analysis and recommendations. It contributes to current development discourse by offering context-sensitive insights aligned with Agenda 2063 and the United Nations Sustainable Development Goals (SDGs). While existing literature often focuses on broad regional frameworks, it frequently overlooks localized strategies that reflect national differences in policy capacity, institutional strength, and resource endowment. This study adopts a qualitative, library-based research methodology, utilizing document analysis to examine secondary data obtained from peer-reviewed journals, institutional reports, and credible development databases such as AfDB, UNECA, and UNDP. Findings reveal that countries integrating sustainable development principles, such as Morocco, Rwanda, and Ghana achieve improved governance, economic diversification, and social inclusion. Accordingly, the study recommends strengthening institutional capacity, investing in green infrastructure and human capital, and expanding intra-African trade under AfCFTA. Future research should explore the long-term impacts of localized reforms and assess the role of digital innovation and climate finance in Africa’s transformation.